2011
DOI: 10.1631/jzus.b1000285
|View full text |Cite
|
Sign up to set email alerts
|

HLA polymorphism of the Zhuang population reflects the common HLA characteristics among Zhuang-Dong language-speaking populations

Abstract: A study of the human leukocyte antigen (HLA) genetic characteristics in the Zhuang, the largest ethnic population in China, would provide insight into Zhuang history and give a useful tool for disease associations, transplantation, and anthropology. In the present study, we report the comprehensive HLA-A, HLA-B, HLA-C, and HLA-DRB1 alleles and haplotypes in the Zhuang population of southern China for the first time. A total of 13 HLA-A, 24

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
10
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 35 publications
6
10
0
Order By: Relevance
“…A clear difference in HLA allele distribution between the northern and southern ethnic groups in China was found previously for the Hui , Tibetans , Menbas and Mongolians from the north and the Bulang , Hani , Buyi , Dai , Jinuo , Wa , Maonan , Miao and Zhuang from the south. The HLA‐A alleles, A*02:03, A*02:07 and A*11:01, were more common in the southern groups than in the northern groups (0.09 vs 0.02, 0.11 vs 0.04 and 0.34 vs 0.16, respectively, P < 0.05).…”
Section: Resultssupporting
confidence: 69%
See 2 more Smart Citations
“…A clear difference in HLA allele distribution between the northern and southern ethnic groups in China was found previously for the Hui , Tibetans , Menbas and Mongolians from the north and the Bulang , Hani , Buyi , Dai , Jinuo , Wa , Maonan , Miao and Zhuang from the south. The HLA‐A alleles, A*02:03, A*02:07 and A*11:01, were more common in the southern groups than in the northern groups (0.09 vs 0.02, 0.11 vs 0.04 and 0.34 vs 0.16, respectively, P < 0.05).…”
Section: Resultssupporting
confidence: 69%
“…For example, HLA‐A*01:01 was common in the northern ethnic groups, but absent in all the southern groups except the Buyi. Similarly, HLA‐B*15:02 was common in the southern groups (0.13), but was either absent or rare in the northern groups ( P < 0.03) .…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…The allele frequency of HLA‐B * 15 : 02 ranged from 4.25% to 15.36% in the 9 ethnic populations evaluated. The allele frequencies database indicated that the B * 15 : 02 frequency in the north Han and south Han populations was 1.9% and 7.1%, respectively, which was similar to the allele frequencies of HLA‐B * 15 : 02 previously reported in the Dai, Yi, Miao, Lisu, Hani, and Zhuang populations. Another study regarding the Lisu minority demonstrated that the B * 15 : 02 frequencies were different from those found in this study (5.77%/156 vs 12.3%/111; P < .05).…”
Section: Discussionsupporting
confidence: 85%
“…In China, the Chinese‐speaking Han nationality accounts for approximately 94% of total population, and the Zhang population is the second largest ethnic group in China with a population of approximately 16.2 million. Most of the Zhuang individuals live in the Guangxi Zhuang Autonomous Region in southern China (Shi et al., ). Another important ethnic minority is the Dong population mainly living in south China, with approximately 298,700 members in Guangxi.…”
Section: Introductionmentioning
confidence: 99%